Perlindungan kepada mangsa penderaan seksual kanak-kanak: Kajian di Brunei Darussalam / Nurul Munirah Awang Jumat - Nurul Munirah , Awang Jumat (2019)

(untitled)
Violence against children is a frequently discussed issue globally. The United Nations Convention on the Rights of the Child (UNCRC) 1989 is one of the conventions by the United Nations Children’s Fund (UNICEF) which is ratified by Brunei on 27 Disember 1995. It is a comprehensive document detailing issues relating to human rights and child protection. Brunei as a nation of Malay Islamic Monarchy ideology is also of no exception to dealing with child abuse cases in the forms of physical, sexual, emotional and child neglect. This study concentrates on the protection of sexually abused children from the perspectives of social welfare and legislation in Brunei. Sexual abuse is somewhat difficult to study as it is a hidden social problem in comparison to other forms of abuse. The objective of this study is to identify the risk factors and the effects of sexual abuse children, based on the cases reported to the relevant government agencies in Brunei. Furthermore, this is also to study the laws and efforts undertaken by the government agencies in providing protection to abused children and legal punishment on the perpetrator. To achieve the objectives, several methods were used including library research, interviews and document research. The outcome of the research shows that sexual abuse children marked a substantial difference between reported and unreported cases. The informants agreed that there are still many more sexual abuse cases that went unreported to the authorities. All the informants unanimously agreed that sexual abuse happens due to the combination of various factors and that the impact on the victims would encompass the psychology, behavioural and physical aspects. Brunei current laws pertaining to issues surrounding child sexual abuse are adequately implemented. In an effort to curb sexual abuse incidence, Brunei has a protection system in place, carried out in collaboration with government agencies in line with their own roles and responsibilities. This protection is also specified in the law, particularly the Children and Young Persons’ Act Chapter 219 (CYPA CAP.219) which is used as a legal policy that covers any matters relating to children. Apart from that, the Brunei Penal Code Chapter 22 and the Brunei Syariah Penal Code Order 2013 provisioned punishments to the perpetrator for sexual crimes. This shows that Brunei is looking into this matter seriously and has established methods and solutions towards providing proper and necessary protection for the children in the country.